Vaginal Vault Closure Techniques in Total Laparoscopic Hysterectomy: A Comparison Between Laparoscopic Route Vault Suturing and Vaginal Route Suturing - Kanupriya Singh; Bhavit Shah; Vipul Patel; Mihir Goswami; M B Shah (Medsci Publications, 2011)
Objective:  To study and compare the two approaches for vaginal vault closure in patients undergoing total laparoscopic hysterectomy. Material and methods: A comparative study was undertaken in 70 patients who underwent total laparoscopic hysterectomy for benign gynaecological disorders in Kesar SAL medical college, Ahmedabad. In half of the patients, vault closure was done through laparoscopic route and in the other half it was done through vaginal route. Results: The group who underwent vaginal vault suturing by laparoscopic route, the mean operative time was 77.0 (+6.4 SD, range 70-94) minutes as compared to the group in which vaginal vault were sutured through vaginal route (88.5 minutes with a SD +4.9, range 80 - 100), the observed difference was statically significant (p <0.00). The post operative vaginal length was better preserved in laparoscopic suturing (8.4 cm with a SD of +0.4, range 8.5 - 10) as compared to vaginal suturing (7.34 cm with a SD of + 0.4, range 7.5 - 9.2) and difference was statically significant (p <0.00). Post operative complications were also statically significantly lower in the laparoscopic route vault closure (28.5%) as compared to vaginal route vault closure (88.5%) and difference was statically significant (Z= 6.42, p < 0.000). Conclusion: laparoscopic route vault closure was less time consuming and comparatively safer than vaginal route vault closure.